Epigenetics Protocols - Tollefsbol, Trygve O.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
The field of epigenetics has played a major role at the forefront not only of molecular biology, but also of medical genetics and clinical medicine.  Few disciplines have experienced growth comparable to that which we have witnessed for epigenetics in the past decade. The goal of Epigenetics Protocols, Second Edition is to highlight select techniques that have been mainstays in the field as well as to cover methods that are especially relevant to extant discoveries in epigenetics.  This volume focuses on the two broad areas of epigenetics: DNA methylation and chromatin modifications, and also covers the complex topic of computational methods for epigenetic analyses which is essential to a complete understanding of the vast body of information that is being derived with the use of these newly-developed tools.  Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and accessible, Epigenetics Protocols, Second Edition serves as an ideal guide to advanced students, basic scientists and clinical researchers as well as clinicians and biotechnology investigators who wish to continue exploring this exciting and progressive research field.
Advances in Epigenetic Technology -- DNA Methylation Detection: Bisulfite Genomic Sequencing Analysis -- Methylation-specific PCR (MSP) -- Analyzing DNA Methylation Using Bisulfite Pyrosequencing -- Closed-tube PCR Methods for Locus Specific DNA Methylation Analysis -- A Combined Bisulfite Restriction Analysis (COBRA) Bioinformatics Tool:  Methyl-typing -- SIRPH:  an HPLC-based SNuPE for Quantitative Methylation Measurement at Specific CpG Sites -- Restriction Landmark Genome Scanning (RLGS) -- Methylated DNA Immunoprecipitation (MeDIP) Genome-wide Analysis -- Methylated-CpG Island Recovery Assay (MIRA) -- Global DNA Methylation Analysis Using the Luminometric Methylation Assay, LUMA -- Inhibition of DNA Methylation in Somatic Cells -- DNA Methyltransferase Assays -- A Chromatin Immunoprecipitation Protocol for Small Cell Numbers -- Native Chromatin Immunoprecipitation (nChIP) -- Q-PCR in Combination with ChIP Assays to Detect Changes in Chromatin Acetylation -- Sequential Chromatin Immunoprecipitation (SeqChIP) Assay and Analysis -- Combined Chromatin Immunoprecipitation and Bisulfite Methylation Sequencing (ChIP-BMS) Analysis -- Studying RNA-protein Interactions in vivo by RNA Immunoprecipitation (RIP) -- Using ChIP-seq Technology to Generate High-resolution Profiles of Histone Modifications -- Mapping Open Chromatin with Formaldehyde-assisted Isolation of Regulatory Elements (FAIRE) -- Inhibition of Histone Deacetylases -- Computational Methods for Epigenetic Analysis - the Protocol of Computational Analysis for Modified Methylation-specific Digital Karyotyping (MMSDK) Based on Massively Parallel Sequencing.
Keywords: Human genetics; Gene expression; Human Genetics; Gene Expression